Church funeral as the expression of Christian faith – actually binding norms - DYDUCH, JAN MACIEJ (Prawo Kanoniczne, 2018)
A ceremony of church funeral should be performed in the way that would express the truth about the Risen Christ and about the redemption of our bodies and eternal life. Canonical norms regulating the matter to whom the church funeral should be granted or not have been changed in the recent dozens of years. The change was from the rigorous model to more moderate especially in the case of the suicides or the Faithfull who had chosen the cremation of their bodies. The church legislation prefers traditional burial but permits cremation provided that the choice does not demonstrate a denial of faith in the resurrection of the body.